Photoemission study of the electronic structure of LaFeAsO 1-xFx and LaFePO1-xFx - Malaeb, Walid (2008)
We have performed a photoemission spectroscopy study of the newly discovered iron-based superconductors LaFeAsO1-xFx and LaFePO1-xFx. The valence-band spectra show a narrow Fe 3d-derived band near EF indicating the itinerant character of the Fe 3d states. In going from the undoped to F-doped compounds, all the spectra are found to shift to higher binding energies, consistent with electron doping within the rigid-band model. Also, in going from LaFeAsO1-xF x to LaFePO1-xFx, the near-EF intensity increases reflecting the weakening of electron correlation.